Business law - Miller, Roger LeRoy (Thomson/West, 2008)
Concise, straightforward, and student-friendly, BUSINESS LAW: TEXT AND EXERCISES captures basic business law in a practical manner that you will appreciate from the very first chapter. As part of the Advantage Series from West Legal Studies in Business, this paperback workbook is one of the most cost-effective and efficient choices for your business law survey course. The Fifth Edition is specifically designed to help you master the legal concepts and doctrines presented, and to give you experience in applying basic legal principles to common business situations. Hypothetical examples are used for illustration rather than real court cases. A 2008 Online Legal Research guide, included FREE with every text, provides basic information about how to find almost anything related to law on the internet. With this proven formula for success, BUSINESS LAW: TEXT AND EXERCISES continues to be the most approachable and practical text you'll find!